Recent advances in medical therapies for pituitary adenomas - Tritos, Nicholas A (International journal of endocrine oncology, 2017)
Together with the recognition of clinical effectiveness of medical therapy, there is a growing awareness of potential risks of DA therapy, including the rare but potentially devastating development of impulse control disorders as well as the potential risk of cardiac valvulopathy associated with the administration of high cumulative doses of cabergoline or pergolide (the latter having been withdrawn in many countries) (5-7). Of note, SSAs are also helpful in achieving local tumor control postoperatively, and can also be effectively used as primary medical therapy in select cases, including patients whose tumors are distant from the optic chiasm and are unlikely to be cured by surgery because of tumor location and size, as well as patients who decline surgery (9). Of note, several novel therapies are being evaluated in clinical trials (Phase II-III) in patients with acromegaly, including an orally absorbed octreotide formulation (octreolin), a liquid crystal octreotide depot preparation (CAM2029), a pan-selective SSA (DG3173) and an antisense oligonucleotide (ATL1103) that inhibits GH receptor synthesis (12). [...]medical therapy has been used to optimize the medical status of severely ill patients with CD before they undergo TSS, or in a small number of patients with hypercortisolism whose tumor location remains uncertain despite extensive investigations.